To Compare the Recurrence Rate of Pterygium Excision with Bare-sclera, Free Conjunctival Auto Graft and Amniotic Membrane Grafts - Abdul Baseer, Naimatullah Khan Kundi, Nazullah Khan, Mushtaq Ahmad (Pakistan Journal of Ophthalmology, 2010)
Purpose: To compare the recurrence rate in pterygium excision with bare sclera, conjunctival auto graft & amniotic membrane grafts. Material and Methods: Patients presenting to the outpatients clinic of ophthalmology department in Khyber teaching hospital with pterygium were included in this study. Total 118 patients were included in this study. These patients were divided into three groups, group-A with bare sclera technique, group-B conjunctival auto graft & group-C amniotic membrane graft. Cases were randomly selected on the basis of inclusion and exclusion criteria and details were recorded on a pre-developed proforma. All patients were operated under sub conjunctival anesthesia, injection xylocaine with adrenaline 0.25 cc was given into the head of pterygium and 0.5 cc of the same injection was administered at the donor site. In bare sclera (group-A) the pterygia were excised, the abnormal tissues were cleared from the sclera & the remaining area including the healthy conjunctiva was left as such. In conjunctival auto graft (group-B), the bare area first measured with caliper. Then the auto graft of the same size was fashioned from the superio-temporal region of the bulbar conjunctiva and sutured with 10/0 nylon to the surrounding conjunctiva. In-group C, after excising the pterygium, the bare area and the conjunctival defects were covered with stitch amniotic membrane grafts using 10/0 nylon suture. At the conclusion, antibiotic drops and ointment were instilled in the eye and the eye was patched for 24 hours. Each patient was followed for a period of six months. The primary outcome was to measure pterygium recurrence. The recurrence is defined as the 2mm or more re-growth of the fibro vascular tissue over the cornea. Results: Total 118 patients were included in this study. Out of the 118 cases, 74 (63%) were male & 44 (37%) were female. 30 patients were operated with bare sclera technique, 34 were with conjunctival auto graft & in 54 eyes amniotic membrane was grafted. 11 i.e. 36.6% recurrence was noted in-group A, in-group B, 3 (8.8%) cases developed recurrence & four (7.40%) developed corneal recurrence in-group C. The ages of the patients ranged from 15-60 years. Conclusion: It was concluded that free conjunctival auto graft & amniotic membrane graft, are better and safe techniques, for prevention of recurrence after pterygium surgery as compared to bare sclera method. Absorbing excessive stem and progenitor cells may be one of the mechanisms of reducing the recurrence rate using amniotic membrane.